Feeder density enhances house finch disease transmission in experimental epidemics. (12th March 2018) - Moyers, Sahnzi C.; Adelman, James S.; Farine, Damien R.; Thomason, Courtney A.; Hawley, Dana M.
Abstract : Anthropogenic food provisioning of wildlife can alter the frequency of contacts among hosts and between hosts and environmental sources of pathogens. Despite the popularity of garden bird feeding, few studies have addressed how feeders influence host contact rates and disease dynamics. We experimentally manipulated feeder density in replicate aviaries containing captive, pathogen-naive, groups of house finches ( Haemorhous mexicanus ) and continuously tracked behaviours at feeders using radio-frequency identification devices. We then inoculated one bird per group with Mycoplasma gallisepticum (Mg), a common bacterial pathogen for which feeders are fomites of transmission, and assessed effects of feeder density on house finch behaviour and pathogen transmission. We found that pathogen transmission was significantly higher in groups with the highest density of bird feeders, despite a significantly lower rate of intraspecific aggressive interactions relative to the low feeder density groups. Conversely, among naive group members that never showed signs of disease, we saw significantly higher concentrations of Mg-specific antibodies in low feeder density groups, suggesting that birds in low feeder density treatments had exposure to subclinical doses of Mg. We discuss ways in which the density of garden bird feeders could play an important role in mediating the intensity of Mg epidemics. This article is part of the theme issue 'Anthropogenic resource subsidies and host–parasite dynamics in wildlife'.